북미협상의 진전과 한국의 중재: 한국의 유인책과 북미의 이익 부합 - 고광영; Kwang-young Ko (한국과 국제정치, 2024)
이 연구의 목적은 북미협상에서 한국의 중재 시도가 상반된 결과를 야기했던 사례들에 주목하여, 그 결과의 차이를 가져오는 조건을 모색하는 것이다. 국제정치이론의 중재 이론 중 제3국의 레버리지 활용 논의에 기반하여 ‘유인책 제시’ 가설을 도출하였고, 이를 한국이 중재를 시도했던 다섯 사례에 적용하여 검증하였다. 제3국의 중재에 있어서 레버리지 활용 여부는 갈등 당사국들로 하여금 손익계산을 새롭게 하여 중재의 성패를 좌우할 수 있는 주요 변수로 평가된다. 그중에서도 제3국의 유인책은 양국을 이익확보 차원에서 협상으로 유인하는 역할을 한다. 경험적 분석의 결과, 한국이 북미 모두의 이익에 부합하는 유인책을 제시했을 경우에 북미협상이 진전되었고, 유인책이 북미 중 한쪽의 이익에만 부합하거나 모두의 이익에 부합하지 않는 절충안을 제시했을 경우에는 북미협상이 진전되지 않았다. 이 연구는 북미협상을 다룬 기존 연구에서 제시하지 않았던 ‘한국의 중재 역할에 대한 일반화된 설명’을 시도한다는 점에서 그 의의가 있다. The purpose of this article is to explore the conditions that brought different outcomes of South Korea’s mediation in the nuclear bargaining between the United States and North Korea. Based on the disscusion on the leverage by third-party in international mediation theory, ‘Inducement Offers’ hypothesis is presented and tested through five cases of South Korea’s attempts to mediate in the nuclear bargaining. Whether to use leverage in mediation by third-party is considered a key variable that determines the success or failure of mediation by allowing the conflicting parties to update their profit and loss calculation. Among the leverage, inducement plays a role in inducing them to bargain in order to obtain their benefits. According to the empirical analysis of this article, when South Korea offers inducements that suited the interests of both the United States and North korea, it is likely that the bargaining moves to the next phase, and otherwise, the bargaining does not move forward. This artcile contributes to the existing literature by providing a generalized explanation for South Korea’s mediation role which previous studies have not attempted.